Using self-assessment as a tool for English language learning - Mohamed Jamrus, Mohd Hafizuddin; Mohamed Razali, Abu Bakar (Canadian Center of Science and Education, 2019)
A very important element of formative assessment is giving and receiving feedback. However, most teachers face difficulty in giving students feedback due to various reasons, such as the large number of students in class that makes it time consuming for them to do so. Fortunately, students themselves can be excellent sources of feedback through self-assessment, through which the students would reflect on the quality of their work, judge the degree to which their work reflects explicitly stated goals or criteria, and revise their work if necessary. Under the right conditions, student self-assessment can provide accurate, useful information to promote learning. Self-assessment can also be effective in English language learning, such as: motivating students to learn and reflect on their own English learning; promote critical thinking and reflective practices in learning English; scaffold knowledge of English learning from different English language skills; develop a sense of autonomy in their own learning English; and foster commitment in learning English among many others. This conceptual paper thus seeks to explore the potentials of using self-assessment in English language learning. In this paper, the concept and underlying principles of self-assessment will be introduced. Next, the review of past studies on self-assessment in the context of teaching and learning English as a second or English as a foreign language (ESL/EFL) will be explained. Later, the advantages and disadvantages of using self-assessment in the classroom will be discussed. In the final section, recommendations will be given for the implementation of self-assessment in learning English as a second language (ESL) classrooms.